Electrocardiogram predictors of multivessel disease in ST-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention - Ajay Kumar Sharma (Research in Cardiovascular Medicine, 2021)
Objective: The objective was to study the role of 12-lead electrocardiogram (ECG) changes in predicting the association of severe stenosis of other coronary arteries along with infarct-related artery in patients who presented with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Materials and Methods: We studied the admission ECG, clinical records, and coronary angiography of 201 patients with STEMI who underwent primary PCI within the first 12 h of symptoms. Patients with first episode of STEMI and coronary angiogram showing coronary artery disease between January 2015 and July 2016 were included in this study. Results: Most of the patients in this study were males (82.1%). The mean age of the patients was 55.20 ± 11.79 years. Diabetic mellitus (37.8%), hypertension (37%), and smoking (49.7%) were the main risk factors. This study had 117 (58.2%) patients of anterior wall myocardial infarction (MI) (Group I) while inferior wall MI was present in 84 (41.8%) patients (Group II). In Group I, 83 (70.9%) patients had single-vessel disease (SVD) while 34 (29.1%) patients had multivessel disease (MVD). The presence of ST-segment depression ≥0.1 mV in leads I, aVL, and V6 significantly correlated with the presence of MVD (P = 0.001, 0.001, and 0.001, respectively). In Group II, 39 (51.3%) patients had SVD while 37 (48.7%) patients had MVD. The presence of ST-segment depression in leads aVL, V5, and V6 significantly correlated with the presence of MVD (P = 0.049, 0.001, and 0.001, respectively). Conclusion: The presence of ST-segment depression of ≥0.1 mv in leads I, aVL, and V6 on admission ECG in the setting of acute anterior wall STEMI and in leads aVL, V5, and V6 on admission ECG in the setting of acute inferior wall STEMI was associated with MVD.